DIFRAKSI GELOMBANG PADA SILINDER 8ESAR DENGAN MILD SLOPE EQUATION - Purwantoro, Didik (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This research is aimed to know the process of wave diffraction around the large cylinder of offshore structure using finite element method. This model chosen because of some reasons, i.e the complication of offshore structure's shape which are caused difficulties to conduct physical model solving. The other excess of this numerical model is cheaper and easier than physical model conducted in the laboratorium. The equation of wave diffraction can be formulated as Helmholtz equation. A second approach can be developed by Mild Slope Equation, which is assumed that the depth is constant. The Helmholtz equation was done using finite element method with linear triangle interpolation. With finite element method, the complicated domain area can be solved more easily and effectively. The result shows that the use of finite element method is still adequate to solve Helmholtz equation' for period 8, 9 and 10 second. For period of 8 second numerical error produce the wave height difference of 0,36 m. The numerical model is then easily edited to analyze another offshore structures. Keywords: diffraction, cyllinder, finite element